2013
DOI: 10.1371/journal.pone.0068305
|View full text |Cite
|
Sign up to set email alerts
|

Gene Transfection in High Serum Levels: Case Studies with New Cholesterol Based Cationic Gemini Lipids

Abstract: BackgroundSix new cationic gemini lipids based on cholesterol possessing different positional combinations of hydroxyethyl (-CH2CH2OH) and oligo-oxyethylene -(CH2CH2O)n- moieties were synthesized. For comparison the corresponding monomeric lipid was also prepared. Each new cationic lipid was found to form stable, clear suspensions in aqueous media.Methodology/Principal FindingsTo understand the nature of the individual lipid aggregates, we have studied the aggregation properties using transmission electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 57 publications
(55 reference statements)
1
18
0
Order By: Relevance
“…(3) FBS played pivotal role in the transportation of polyplexes which eventually results in effective transfection. It indicated that P123-PPI/pDNA polyplexes had significant serum dependent transfection activity, which was consistent with the results obtained from the other report [40]. The transfection efficiency of P123-PPI/pDNA polyplexes showed a 'bell'-shaped serum concentration dependence behavior when FBS percentage increased from 5 to 50% (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…(3) FBS played pivotal role in the transportation of polyplexes which eventually results in effective transfection. It indicated that P123-PPI/pDNA polyplexes had significant serum dependent transfection activity, which was consistent with the results obtained from the other report [40]. The transfection efficiency of P123-PPI/pDNA polyplexes showed a 'bell'-shaped serum concentration dependence behavior when FBS percentage increased from 5 to 50% (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Other groups have reported the electrostatic interaction when the GCL contains an oligo-oxyethylene spacer [93,115], and/or other headgroups as imidazolium or pyridinium [45, 57-59, 75, 99, 116]. Looking for more biocompatible vectors, GCLs that incorporate aminoacid rests, such as GCL-lysine 12 based and GCL-arginine based [60,62,64], GCL-cholesterol based [117][118][119], and GCL-cyclen-based [120] have been also investigated. Lipoplexes containing a MVCL with dendritic-type headgroup have been also analyzed [67,121,122].…”
Section: Electrostatic Interactionmentioning
confidence: 99%
“…TEM and/or cryo-TEM studies have reported many micrographs to characterize the size, shape, and morphology of a wide variety of lipoplexes as: (a) pDNA with GCLs [45,54,57,62,64,75,93,115,117,118,120], MVCLs [63], cationic polymers [107,133,[169][170][171] or polycations [40,84,100,136]; and (b) siRNA with cationic polymers [90,104]. Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations